Implementasi Profil Pelajar Pancasila Dalam Menghadapi Perundungan Di Sekolah Dasar: Perspektif Glokalisasi - Kamalin, Lina; Mariana, Neni; Subrata, Heru (LP. Ma'arif Janggan Magetan, 2024)
Profil Pelajar Pancasila is a Standar Kompetensi Lulusan (SKL) it is mean a Graduate Competency Standard which refers to the character and competencies that Indonesian students are expected to have. This profile consists of six dimensions: faith, devotion to God Almighty, noble character; global diversity; collaboration; creativity; critical thinking; and independence. This profile reflects the quality of the generation by the National Education Goals and acts as the main reference that directs education policies. Character is the main part that must be built to realize student welfare. However, on the other hand, the results of the National Assessment through the 2022 Character Survey show that the rate of bullying is still quite high, namely 36.31% of students have the potential to experience bullying, which means 1 in 3 children experience bullying at school. This research method is a position paper with a literary study approach, aimed at conveying the author's view or position on a particular topic or issue. In this research, starting with identifying issues or problems related to the Pancasila student profile and its application to overcome bullying in educational units is the first step in this research project. In addition, this research aims to investigate the glocalization process in the profile of Pancasila students by collecting evidence using literary studies.